1992
DOI: 10.1002/lsm.1900120106
|View full text |Cite
|
Sign up to set email alerts
|

Detection of calcified atherosclerotic plaque by laser‐induced plasma emission

Abstract: The use of fluorescence spectroscopy to discriminate atherosclerotic from normal tissue is limited by a lower sensitivity for calcified than noncalcified atherosclerotic plaque (65% vs. 93%, respectively). To evaluate plasma emission as a means to detect calcified plaque, 325 normal and atherosclerotic cadaveric aortic sites were irradiated through a 100-micron silica fiber in blood by a pulsed holmium laser (lambda = 2.1 microns, fluence = 4 J/mm2). A photodiode positioned near the proximal end of the fiber d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In 1985, Kittrell and colleagues [26] reported normal arterial wall in vitro by analyzing autoa spectrofluorimeter. Subsequently, various lasers were used as light Sources for the in vitro excitation of arterial fluorescence: an argon ion laser operating at 458 nm [27], a nitrogen laser at 337 nm [28, 291, a dye laser emitting between 305 and 310 nm [301 or at 476 nm ~311, or a H~-c~ laser operating at 325 nm [32][33][34][35][36]. The H~-c~ A two-laser system with a dye laser emitting at a of480 nm for tissue ablation and autofluorescence has been evaluated in patients with peripheral vascular disease of the lower ex-and for lipid plaques were essentially the Same as according to algorithm (I1) for media and lipid that a fibrous plaque could be differentiated from fluorescence spectra after excitation a t 480 nm in lesions in cave knee, there was a peak at 470 nm followed by laser was also used in viva on humans [37].…”
Section: Arterial Spectra In Bloodmentioning
confidence: 99%
“…In 1985, Kittrell and colleagues [26] reported normal arterial wall in vitro by analyzing autoa spectrofluorimeter. Subsequently, various lasers were used as light Sources for the in vitro excitation of arterial fluorescence: an argon ion laser operating at 458 nm [27], a nitrogen laser at 337 nm [28, 291, a dye laser emitting between 305 and 310 nm [301 or at 476 nm ~311, or a H~-c~ laser operating at 325 nm [32][33][34][35][36]. The H~-c~ A two-laser system with a dye laser emitting at a of480 nm for tissue ablation and autofluorescence has been evaluated in patients with peripheral vascular disease of the lower ex-and for lipid plaques were essentially the Same as according to algorithm (I1) for media and lipid that a fibrous plaque could be differentiated from fluorescence spectra after excitation a t 480 nm in lesions in cave knee, there was a peak at 470 nm followed by laser was also used in viva on humans [37].…”
Section: Arterial Spectra In Bloodmentioning
confidence: 99%
“…Fluorescence [14], [15] and plasma luminescence [16]- [18] have been used for detection of calcified atherosclerotic plague with high sensitivity in angioplasty. A major drawback of using fluorescence spectroscopy is interference with blood clots and need for additional diagnostic light source [14], [17]. Plasma luminescence during pulsed laser ablation leads to a characteristic spectrum determined by tissue composition, A major disadvantage for longer pulse ablation system in using luminescence spectra in tissue diagnosis is that it requires an ablative laser fluence which might not be well-suited since it causes significant thermaVmechanical damage to the surrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of targeted drug delivery was first elaborated by Paul Ehrlich in the early 20 th century [Himmelweit, 1957]. Recent efforts to effect targeted delivery include local photosensitizer administration [Amano et al, 1988], intra-arterial drug administration [Deckelbaum et al, 1990], choice of route of administration [Bachor et al, 1992], photosensitizer activation with green visible light to avoid substantial normal tissue penetration [Nseyo et al, 1993;Veenhuizen et al, 1997], and two-photon excitation in the near-infrared [Fisher et al, 1997]. It has been suggested that the inherently lower pH of many tumors [Wike-Hooley et al, 1984;Thistlethewaite et al, 1985] may be exploited to identify photosensitizers with preferential tumor uptake [Pottier and Kennedy, 1990].…”
Section: Current Developmentsmentioning
confidence: 99%